2018
DOI: 10.1002/cncr.31296
|View full text |Cite
|
Sign up to set email alerts
|

Decreased early mortality associated with the treatment of acute myeloid leukemia at National Cancer Institute‐designated cancer centers in California

Abstract: The initial treatment of adult patients with AML at NCI-CCs is associated with a 53% reduction in the odds of early mortality compared with treatment at non-NCI-CCs. Lower early mortality may result from differences in hospital or provider experience and supportive care. Cancer 2018;124:1938-45. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…Asians and women are known to have a higher prevalence of EGFR mutations (59,60), which explains our finding of an increased likelihood of TKI use in these groups. We also observed that patients treated at NCI-designated centers were more likely to receive any systemic treatment and TKIs, consistent with studies that have observed better adherence to guideline concordant care at NCI-designated cancer centers (61,62). However, NCI designation did not affect the likelihood of receiving treatment with bevacizumab.…”
Section: Discussionsupporting
confidence: 88%
“…Asians and women are known to have a higher prevalence of EGFR mutations (59,60), which explains our finding of an increased likelihood of TKI use in these groups. We also observed that patients treated at NCI-designated centers were more likely to receive any systemic treatment and TKIs, consistent with studies that have observed better adherence to guideline concordant care at NCI-designated cancer centers (61,62). However, NCI designation did not affect the likelihood of receiving treatment with bevacizumab.…”
Section: Discussionsupporting
confidence: 88%
“…Two recent studies reported significantly higher early mortality rates among patients treated in non-academic versus academic centers, and in non-NCI-designated versus NCI-designated cancer centers 166,167 . In a National Cancer data Base of 60,738 patients with AML, the 1-month mortality was 16% in academic centers and 29% in non-academic centers (p < 0.001), and the 5-year survival rate was 25% versus 15 % (p < 0.001) 166,167 . The second study from California in 7007 patients with AML reported an early mortality rate in AML of 12% in NCIdesignated cancer centers versus 24% in non-NCIdesignated cancer center 167 .…”
Section: Translating the Published Literature Into Realworld Experiencementioning
confidence: 99%
“…81 A second study of 7007 patients reported an early mortality rate of 12% in NCI-designated cancer centers versus 24% in non-NCI-designated cancer centers. 82 At MD Anderson, the 4-week mortality rate with intensive chemotherapy is <5%; the early mortality rate with low-intensity regimens in older patients with AML is 2% to 3%. Whenever logistically possible, we encourage AML treatment in leukemia centers of excellence.…”
Section: How To Choose Between Intensive and Lower-intensity Chemothementioning
confidence: 99%